Hubungan Persepsi Bimbingan Karir dengan Motivasi Bekerja pada Siswa Kelas XI Sekolah Menengah Kejuruan (SMK) di Sidoarjo - Suliani, Likis; Laili, Nurfi (Indonesian Journal Publisher, 2023)
This research is motivated by the phenomenon of vocational school graduates who are unemployed, and many students do not know their future goals. The purpose of this study was to determine the relationship between career guidance perceptions and work motivation in class XI students of vocational high school (SMK) in Sidoarjo. The method used in this research is quantitative with a correlational approach. The data collection technique in this study used a psychological scale with a Likert scaling model, namely the career guidance perception scale and work motivation scale. The population in this study were 64 students of class XI SMK TPI Gedangan Sidoarjo. Determination of the research sample using total sampling, so that the research sample was taken from the total population, as many as 64 students. Data analysis was carried out using Spearman's Rho Product Moment correlation technique using the SPSS 25 for windows program. The results of data analysis showed a correlation coefficient of 0.996 with a significance of 0.000 <0.05, meaning that there was a positive relationship between perceptions of career guidance and work motivation.